Reason and Modernity, Critique of Reason and Late Postmodernity: New Symptoms of the Martyrial Turn of Sacrifice - del Valle, Carlos (2021)
The main thesis raised here is that the use made of reason in the civilizing project of the illustration allows the installation of new modes of truth production that will be typical of modernity as a supposed overcoming of pre-modern thought. The critique of reason and the fundamental questions to the civilizational project and the colonial matrix of the enlightenment and modernity are the best evidence of its emptying, all of which will be expressed in postmodern, postcolonial, and decolonial thought. In what way does this suppose a return to certain matrices is considered pre-modern? The work has four sections. The first deals with the fundamentals of illustration understood as an overcoming of the minority through reason. The second section analyzes the dialectic of illustration as a framework for overcoming reason. The third attempts to explain how we can understand the dialectic of the Enlightenment as foundations of postmodernity, in the same way, that Enlightenment operated as the foundation of modernity. Finally, in the fourth section, the distinction between sacrifice and martyrdom is developed, regarding the recent popular resistance movements, which place postmodernity in a process of returning to a matrix that was once considered premodern. In this sense, premodernity and postmodernity are nothing more than an oxymoron of modernity.